2015
DOI: 10.3389/fpls.2015.01074
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Sequencing Technologies: The Doorway to the Unexplored Genomics of Non-Model Plants

Abstract: Non-model plants i.e., the species which have one or all of the characters such as long life cycle, difficulty to grow in the laboratory or poor fecundity, have been schemed out of sequencing projects earlier, due to high running cost of Sanger sequencing. Consequently, the information about their genomics and key biological processes are inadequate. However, the advent of fast and cost effective next generation sequencing (NGS) platforms in the recent past has enabled the unearthing of certain characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(112 citation statements)
references
References 108 publications
0
104
0
Order By: Relevance
“…Significance is identified and expressed as posterior probability of differential expression (PPDE) $0.95 (Leng et al, 2013; Supplemental Files S1-S3, S6). RT-qPCR was not used to validate gene expression due to the prerequisite for highly characterized sequence data (Unamba et al, 2015). A number of criteria need to be met for qPCR reference genes to be regarded as reliable (Chervoneva et al, 2010), importantly, traditional "housekeeping" genes (such as b-actin and 18S) have been extensively acknowledged as unstable in numerous biological systems (Gorzelniak et al, 2001;Solanas et al, 2001;Glare et al, 2002;Raaijmakers et al, 2002;Brunner et al, 2004;Gonçalves et al, 2005;Nicot et al, 2005;González-Verdejo et al, 2008;Barsalobres-Cavallari et al, 2009;Paolacci et al, 2009;Xu et al, 2012b;Jiang et al, 2014;Llanos et al, 2015).…”
Section: De Novo Assemblymentioning
confidence: 99%
“…Significance is identified and expressed as posterior probability of differential expression (PPDE) $0.95 (Leng et al, 2013; Supplemental Files S1-S3, S6). RT-qPCR was not used to validate gene expression due to the prerequisite for highly characterized sequence data (Unamba et al, 2015). A number of criteria need to be met for qPCR reference genes to be regarded as reliable (Chervoneva et al, 2010), importantly, traditional "housekeeping" genes (such as b-actin and 18S) have been extensively acknowledged as unstable in numerous biological systems (Gorzelniak et al, 2001;Solanas et al, 2001;Glare et al, 2002;Raaijmakers et al, 2002;Brunner et al, 2004;Gonçalves et al, 2005;Nicot et al, 2005;González-Verdejo et al, 2008;Barsalobres-Cavallari et al, 2009;Paolacci et al, 2009;Xu et al, 2012b;Jiang et al, 2014;Llanos et al, 2015).…”
Section: De Novo Assemblymentioning
confidence: 99%
“…The transcriptome analysis identified three unique putative genes for AACT (e-value: 1e −48 to 0) and four for HMGS (e-value: 1e −30 to 0) in rose-scented geranium. A total of thirteen unique putative transcripts represented NADPH-dependent enzyme- HMGR (e-value: 3e −21 to 0) in rose-scented geranium, which catalyzes the biosynthesis of mevalonate from HMG-CoA [17, 31]. The sequence analysis of putative AACT, HMGS and HMGR genes suggested that they contain full-length open reading frames (ORFs).…”
Section: Resultsmentioning
confidence: 99%
“…Sangwan et al [16] provided a process for isolation of proteins and catalytically active enzymes from rose-scented geranium. Next-generation sequencing (NGS) technologies have accelerated transcriptome investigations in several plant species, exploring qualitative and quantitative insights of global gene regulation [17]. In SRA database, raw sequencing reads are available for a total of 13 Pelargonium species: P. tetragonum , P. fulgidum , P. transvaalense, P. incrassatum , P.austral , P. cotyledonis , P. nanum , P. citronellum , P. dichondrifolium , P. myrrhifolium , P. echinatum , P. exstipulatum , and Pelargonium x hortorum .…”
Section: Introductionmentioning
confidence: 99%
“…20 Different concentrations (3.65-500μg in 20μl of ethanol) were prepared and mixed with (180μl) 50 µM DPPH. Plumbagin in different concentration (0.83-100μM) was used as the reference-standard.…”
Section: Antioxidant Potential In Different Tissuesmentioning
confidence: 99%